A context‐aware internet of things‐driven security scheme for smart homes. Issue 1 (30th September 2022) - Khanpara, Pimal; Lavingia, Kruti; Trivedi, Rajvi; Tanwar, Sudeep; Verma, Amit; Sharma, Ravi
Abstract: In recent years, the Internet of Things (IoT) has become very popular as it has numerous applications in the industrial and research domain. Moreover, the features of IoT systems play a crucial role in the development of smart cities. It enables smart cities and their subsystems to monitor, control, and manage heterogeneous devices remotely by extracting and communicating real‐time data. However, automated IoT systems are vulnerable to many security threats like tempered protocols, device hijacking, and unauthorized access. Motivated by the aforementioned discussion, this paper addresses the security requirements of an essential subsystem of smart city architecture, that is, IoT‐based smart homes. Based on the features and functionalities of smart homes, the risk of security violations in the system behavior needs to be analyzed This paper explores various security threats in a smart home environment and proposes a context‐aware security‐based scheme to prevent and detect possible threats. Results show that the proposed scheme is superior compared to the traditional schemes considering parameters such as the performance, cost, and maintenance requirements.